INDIVIDUAL AND CONTEXTUAL FACTORS OF MALNUTRITION IN MOROCCAN CHILDREN UNDER FIVE - Berrouyne, Mustapha; Hami, Hinde (Bangladesh Journal of Multidisciplinary Scientific Research, 2024)
This study investigates the multifaceted determinants of malnutrition among Moroccan children under five, focusing on individual, household, and community influences. Utilizing data from the 2018 Population and Family Health Survey, the study analyzes 5,983 children aged 0–59 months. This study employs a multilevel modelling methodology to consider the data’s hierarchical structure. The results reveal that 18% of Moroccan children suffer from undernutrition, while 10% experience overnutrition. Factors influencing malnutrition include child sex, age, birth weight, parental education, breastfeeding practices, household size, and poverty. Male children and those with a low birth weight are also at increased risk, with ORs of 1.49 and 1.93, respectively. Parental education, especially maternal education, protects against undernutrition (OR = 1.45). Breastfeeding practices impact child nutrition, with children not breastfed having higher odds of undernutrition (OR = 2.03). Children from poorer households are more likely to suffer from undernutrition (OR = 2.40). Conversely, children from wealthier households are at a higher risk of overnutrition (OR = 1.78). Community-level factors, such as poverty and regional disparities, influence undernutrition outcomes, with notable differences in regions like Beni Mellal-Khenifra (OR = 6.15). Children living in rural areas are more likely to experience undernutrition than their urban counterparts (OR = 1.87). The findings of this study conclude that addressing child malnutrition in Morocco requires multi-level interventions, focusing on parental education, breastfeeding promotion, support for low-birth-weight infants, and targeted strategies for socio-economic and geographic disparities. JEL Classification Codes: I14, I12.